Lesson Learned From the Olweus Bullying Prevention Program and KiVa: A Narrative Review - Ihsana Sabriani Borualogo; Sulisworo Kusdiyati; Hedi Wahyudi (Faculty of Psychology Universitas Gadjah Mada, 2022)
Bullying is a severe problem that affects students’ mental health. The number of bullying incidents in Indonesia is still high, most likely because the country has not had bullying prevention and intervention programs implemented holistically in all aspects at school. Indonesia’s bullying prevention and intervention programs have been primarily implemented sectorally, only for certain students when incidents have been observed. Two bullying prevention intervention programs that have been tested multinationally, the Olweus Bullying Prevention Program and KiVa, have been proven effective. The aims of this study are twofold: to explain the effectiveness and evaluation of these two stated programs and to give insights for Indonesian researchers interested in developing comprehensive bullying intervention and prevention programs. Discussions are focused on developing the prevention and intervention programs, the implementation of the programs, and the evaluation to test program effectiveness. Results show the importance of involving all school components, integration with the school curriculum, national implementation, and using the programs over an extended period. Evaluation of the programs’ effectiveness is also essential, with a randomized controlled trial recommended for doing so.